The mirror and the map: Central Europe in the late prose of Danilo Kiš - Zoric, Vladimir (Institut za knjizevnost i jezik, 2014)
The article examines Danilo Kiš’s essayistic and narrative articulations of the cultural space of Central Europe in the context of dissident debates and the Yugoslav political crisis. In mid-1980s, Kundera’s essay “The Tragedy of Central Europe” sparked a heated debate prompting most writers of the time to take explicit and largely partisan views on Central European identity and its borders in Europe but also within Yugoslavia. However, in his essay “Variations on Central European Themes” and the short stories “The Apatrid” and “The Mirror of the Unknown” Kiš takes a more moderate and remarkably elusive approach which centres on the trauma of Central European Jewry before and during the Second World War. The main argument is that in the essay Kiš does not offer a clear and coherent theoretical platform on Central Europe’s past and cultural diversity but proceeds to develop an imaginative one in his narrative fiction from the same period. This approach enables him to avoid the ideological pitfall of interpreting the Holocaust as a preparatory stage for the final demise of Central Europe during the Cold War. Instead of the trope of the harbinger victim, which addresses the past merely as a mirror of present developments, Kiš stresses the essential inaccessibility of obliteration as a distinctive Central European experience. Perspectives irretrievably lost through rapid obliteration of lives can only be conjured up by an occult mirror of imagination and it is precisely those mirrors that occupy Kiš as a motif in his stories.